Doprowadź wyrażenie do najprostszej postaci.
a) 8xy - (2x - 3)(4y - 5)
b) 2(x+y)-(1- 2x)(1+ 2y)
c) (2x - 3y)(5 + x) +15(y - x)
d) (4a - 1)(2b + 2) + 2b(1 - 2a)
e) (5x - y)(2y - x) - 11xy
f) (2a + b)(a - 1)-(b - 1)(a + 2)​


Odpowiedź :

Odpowiedź:

[tex]a)\ \ 8xy-(2x-3)(4y-5)=8xy-(8xy-10x-12y+15)=\\\\=8xy-8xy+10x+12y-15=10x+12y-15\\\\\\b)\ \ 2(x+y)-(1-2x)(1+2y)=2x+2y-(1+2y-2x-4xy)=\\\\=2x+2y-1-2y+2x+4xy=4x+4xy-1\\\\\\c)\ \ (2x-3y)(5+x)+15(y-x)=10x+2x^2-15y-3xy+15y-15x=\\\\=2x^2-5x-3xy\\\\\\d)\ \ (4a-1)(2b+2)+2b(1-2a)=8ab+8a-2b-2+2b-4ab=4ab+8a-2[/tex]

[tex]e)\ \ (5x-y)(2y-x)-11xy=10xy-5x^2-2y^2+xy-11xy=-5x^2-2y^2\\\\\\f)\ \ (2a+b)(a-1)-(b-1)(a+2)=2a^2-2a+ab-b-(ab+2b-a-2)=\\\\=2a^2-2a+ab-b-ab-2b+a+2=2a^2-a-3b+2[/tex]